Effect of Pisolithus tinctorius on Growth of Eucalyptus tereticornis Seedlings in Nursery Conditions - Bhagyalakshmi, J.; Sujatha, P.; Sreenivasulu, A.; Meru, Elusing; Rao, P. S. (Indian Forester, 2000)
Fertilisation of forest soils with chemical fertilisers is not only expensive but also results in environmental pollution. Therefore, it has become essential to go for a cheaper, natural, effective and environmentally safer resources such as biofertitisers. About 95-99% of soil phosphorus occurs in fohns that is not directly available to plant roots. Further, its mobility in soils is very low. In such conditions mycorrhiza through symbiotic association offers an effective and long lasting remedy by solubilising unavailable phosphorus and converting them into available form, thereby acting as ’biofertilisers’. Pisolithus tinctorius is an ectomycorrhizal fungus living symbiotically with the roots of Eucalyptus. Fruiting bodies of Pisolithus tinctorius were collected from different places and different strains were isolated. Axenic cultures were established on solid and liquid MMN media. From the axenic culture, mycobeads were prepared and applied to the Eucalyptus seedlings. Uninoculated seedlings were maintained as control under identical conditions to compare the growth the biomass. The fungal infected seedlings have better growth and root development.